2015
DOI: 10.1002/jmri.24932
|View full text |Cite
|
Sign up to set email alerts
|

Standardized uptake value and apparent diffusion coefficient of endometrial cancer evaluated with integrated whole‐body PET/MR: Correlation with pathological prognostic factors

Abstract: SUVmax and ADCmin of endometrial cancer derived from integrated PET/MR are inversely correlated and are associated with pathological prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 32 publications
3
44
2
Order By: Relevance
“…). Similar results have been shown regarding other tumors of gynecologic origin, such as ovarian cancer and endometrial carcinoma …”
Section: Current Applications Of Pet/mrimentioning
confidence: 99%
“…). Similar results have been shown regarding other tumors of gynecologic origin, such as ovarian cancer and endometrial carcinoma …”
Section: Current Applications Of Pet/mrimentioning
confidence: 99%
“…Although there was a significant and inverse correlation with ADC min and SUV max (r=-0.677, p<0.001), the SUV max of the primary tumor was associated with disease-free and overall survival rates while ADC min was not. The other study of interest relating to this issue in the literature was reported by Shih et al (28). Although the authors used the data obtained from an integrated PET/MRI system, they similarly found a significant inverse correlation between the SUV max and ADC min of the primary tumor in 36 patients with EC (r=-0.53, p=0.001).…”
Section: Discussionmentioning
confidence: 98%
“…Hybrid PET/MRI enable to measure glucose metabolism and cellular density in tumor by simultaneous FDG, PET, and DWI acquisition. In malignant lesions, inverse correlation was found between SUV and ADC value [91,92]. Volumetric measurement of tumor is highly correlated when comparing the results from PET images and MRI images (both of T2 weighted images and DWI) [93].…”
Section: Complementary Role Of Pet/mr Imagingmentioning
confidence: 98%